Sexual autonomy and contraceptive use among women in Nigeria: findings from the Demographic and Health Survey data - Viswan SP; Ravindran TKS; Kandala NB; Petzold MG; Fonn S (Dove Medical Press, 2017)
Saritha P Viswan,1 T K Sundari Ravindran,1,2 Ngianga-Bakwin Kandala,1,3,4 Max G Petzold,1,5 Sharon Fonn1 1School of Public Health, University of the Witwatersrand, Johannesburg, South Africa; 2Achutha Menon Centre for Health Science Studies, Sree Chitra Tirunal Institute for Medical Sciences and Technology, Trivandrum, Kerala, India; 3Division of Epidemiology and Biostatistics, School of Public Health, University of the Witwatersrand, Johannesburg, South Africa; 4Department of Mathematics, Physics and Electrical Engineering, Faculty of Engineering and Environment, Northumbria University, Newcastle upon Tyne, UK; 5Department of Public Health and Community Medicine, University of Gothenburg, Gothenburg, Sweden Context: The persistent low contraceptive use and high fertility in Nigeria despite improvements in educational achievements calls for an examination of the role of factors, which may moderate the use of modern contraception. This article explores the influence of sexual autonomy on the use of modern contraceptive methods among women and its relative importance compared with other, more traditional, indicators of women’s autonomy such as education and occupation.Data and methods: Data from two Demographic and Health Surveys (DHS), 2008 and 2013, were used in this study. An index of sexual autonomy was constructed by combining related DHS variables, and its association with current use of modern contraception was examined at each time point as well as over time using multivariate regression analysis.Results: The observed prevalence for use of modern contraception was 2.8 and 2.6 times higher among women who had high sexual autonomy in 2008 and 2013, respectively. The corresponding figures for women with secondary or higher education were 8.2 and 11.8 times higher, respectively, compared with women with no education. But after controlling for wealth index, religion, place of residence, autonomy and experience of intimate partner violence (IPV), the likelihood of use of modern contraception was lowered to about 2.5 (from 8.2) and 2.8 (from 11.8) times during 2008 and 2013, respectively, among women with secondary or higher education. The likelihood of use of modern contraception lowered only to 1.6 (from 2.8) and 1.8 (from 2.6) times among women with high sexual autonomy after controlling for other covariates, respectively, during the same period.Conclusion: Sexual autonomy seems to play an important role in women’s use of modern contraceptive methods independent of education and a number of other factors related to women’s status. Sexual autonomy needs to be simultaneously promoted alongside increasing educational opportunities to enhance women’s ability to use modern contraception. Keywords: family planning, sexuality, decision making, education, empowerment, intimate partner violence